2010
DOI: 10.1016/j.mad.2010.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA alterations and reduced mitochondrial function in aging

Abstract: Oxidative damage to mitochondrial DNA increases with aging. This damage has the potential to affect mitochondrial DNA replication and transcription which could alter the abundance or functionality of mitochondrial proteins. This review describes mitochondrial DNA alterations and changes in mitochondrial function that occur with aging. Age-related alterations in mitochondrial DNA as a possible contributor to the reduction in mitochondrial function are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 129 publications
(180 reference statements)
2
72
1
Order By: Relevance
“…We identified and quantified the complexes in Coomassiestained native gels and could show a reduced mitochondrial protein content upon aging. Other parameters of mitochondrial function include the measurement of the rate of oxygen consumption in isolated mitochondria (Hebert et al, 2010). We found that complex I and complex II-dependent respiration in isolated mitochondria was decreased with age, suggesting age-related impairment of mitochondrial function.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We identified and quantified the complexes in Coomassiestained native gels and could show a reduced mitochondrial protein content upon aging. Other parameters of mitochondrial function include the measurement of the rate of oxygen consumption in isolated mitochondria (Hebert et al, 2010). We found that complex I and complex II-dependent respiration in isolated mitochondria was decreased with age, suggesting age-related impairment of mitochondrial function.…”
Section: Discussionmentioning
confidence: 75%
“…Mitochondria have been suggested for decades to be implicated in aging (Harman, 1972), and it has been observed in a variety of organisms and tissues that mitochondrial function declines with age (Navarro & Boveris, 2004;Marcinek et al, 2005;Hebert et al, 2010). In humans, age-related mitochondrial dysfunction has been most often described in skeletal muscle tissue (Boffoli et al, 1994;Short et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This decrease in MRC functions may be caused by mutations in mitochondrial genes (Byrne et al, 1991;Hebert et al, 2010). Indeed, cytochrome oxidase has been observed to alter polypeptide patterns during ageing (Boffoli et al, 1994).…”
Section: Reversible Function Of Mitochondrial Genes During Buddingmentioning
confidence: 99%
“…At the organelle level, senescence accompanies the decrease in mitochondrial respiratory chain (MRC) activity (Byrne et al, 1991). It has been confirmed that one of the main causes of such functional deterioration in mitochondria is the time-related accumulation of DNA damage (Hebert et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation of proteins can inactivate and target them for degradation; oxidative damage to DNA causes single and double strand-breaks, crosslink to other molecules and base modifications, while lipid oxidation can generate membrane disturbances. As described above, mtDNA represents a critical target of oxidative damage since it does not contain histones and it is located in proximity to the production site of ROS (Hebert, Lanza et al, 2010). Once damaged, mtDNA can indirectly amplify oxidative stress since transcription of critical mitochondrial proteins is defective, leading to a vicious cycle of ROS production and eventually triggering cell death.…”
Section: Oxidative Phosphorylation and Energy Productionmentioning
confidence: 99%